Consumers and the brain drain: product design and the gains from emigration - Peter Kuhn; Carol McAusland (Institute for the Study of Labor (IZA), 2008)
We consider the welfare effects of skilled worker emigration in a context where skilled labor plays a role in product design. We show such emigration can benefit the residents left behind, even when consumers' tastes exhibit a form of home bias. This is because emigration improves the design of goods designed by skilled emigrants but consumed in the sending country. In contrast to existing models of beneficial brain drain, our results do not require agglomeration economies, education-related externalities, remittances, return migration, or an emigration lottery. Instead, they are driven purely by differences in market size that induce skilled emigrants to design better products abroad than at home.
urn:nbn:de:101:1-20080723139
Keywords: F22; 330; Brain drain; international labor migration; product quality; Brain Drain; Produktdesign; Produktqualität; Import; Konsumtheorie; Wohlfahrtseffekt; Theorie